HEART DAMAGE IN PREGNANCIES COMPLICATED WITH PREECLAMPSIA: CASE REPORT - Ivo Kjaev; Jovanova, Silvana; Jana Nivicka Kjaeva; Karadjova, Dafina; Irena Aleksioska; Sasha KJaeva; Rosa Spasova; Goran Kocoski (Macedonian Medical Association/ Walter de Gruyter GmbH, 2016)
Introduction. Heart function in pregnancy is a subject of many debates and studies. A large number of epidemiologic studies have found association between preeclampsia and cardiovascular morbidity/mortality. About 5-8% of deliveries are complicated with preeclampsia. Until recently, heart damage associated with preeclampsia has not been studied. A number of heart difficulties only appear long after the reproduction period has en-ded. Preeclampsia increases the risk for B stage (asymptomatic) of heart failure. Case report. A 37-year-old pregnant patient, G2P1 27 weeks of gestation, paid her first visit to the Gynecology Outpatient Clinic. She complained on heavy breathing, difficulty with movement and hypertension. She was referred for further evaluation to the Cardiology Outpatient Clinic with a suspicion of gestational hypertension and heart abnormalities. The pregnancy was evaluated several times at the Out-patient Clinics of Gynecology and Cardiology with the diagnosis of gestational hypertension. Echocardiography showed abnormal heart remodeling. In the 36 g.w laboratory findings showed urine dip stick ++,ТА160/110. The diagnosis was changed to preeclampsia. The patient was delivered with a re-caesarean section because of previous S.C and preeclampsia. Postpartum echocardio-graphy confirmed left chamber hypertrophy with per-sistent hypertension. Results. Clinical cardiovascular complications in preec-lampsia continue long after the pregnancy has ended. Studies show that pregnancies with both early and late preeclampsia have an increased risk for asymptomatic left chamber dysfunction/hypertrophy and essential hypertension in the next 2 years after delivery. If the damages are caught early prevention can be started sooner rather than later before patients become symptomatic (C stage of heart failure).
ПОЈАВА НА СРЦЕВО ОШТЕТУВАЊЕ КАЈ ТРУДНИЦИ СО ПРЕЕКЛАМПСИЈА: ПРИКАЗ НА СЛУЧАЈ
Keywords: preeclampsia; heart damage; echocardiography; pregnancy